Thomson scattering-induced bandgap in planar chiral phononic crystals. (1st March 2023) - Ding, Wei; Chen, Tianning; Chen, Chen; Chronopoulos, Dimitrios; Zhu, Jian; Assouar, Badreddine
Abstract: Releasing the dependence of the low-frequency and broad bandgaps on low stiffness and bulky masses has been an intractable bottleneck. Although inertial amplification is a terrific candidate for addressing the barrier, numerous extended ideas are limited to the classical models, thus, slowing or stalling the advances in this demand. To break this limit, we report a kind of planar chiral phononic crystal based on Thomson scattering. Different from the optimization effect produced in the locally resonant phononic crystals, the mirrored chirality can open a Thomson scattering-induced broad bandgap when the local resonant sub-structure is discarded. In addition, while simplifying the material components, we lower the starting frequency of the bandgap with a virtually unchanged width for the same lattice constant, stiffness and mass. Consequently, the starting frequency of the attenuation can be in the same order of magnitude as the local resonance bandgap, while the width is significantly better than the latter. Our proposal may open a new way to manipulate broadband elastic waves and validate that Thomson scattering is a promising alternative approach and mechanism for bandgap formation.